The good and the successful - Examination of informal learning mechanisms - Hatakka, Linda (My University, 2014)
This thesis strived to find out which informal learning (IL) mechanisms are used the most by the respondents. Additionally, the goal was to know more about the respondents as informal learners and what could explain possible differences. The target was to resolve whether informal learning explains differences in individual performance or, do some other explanations for success exist. Informal learning was to be made more visible, since many are unaware of it. Relevant IL mechanisms that the interviewees could explain were selected for this thesis. The theory on informal learning was presented and some additional informal learning mechanisms were included: Underlying learning theories, internal and external learning resources, as well as some sport related informal learning mechanisms. Various scholars have explained these terms. The final results of this thesis relate to business context, but sport is at the scope of my research. The target group consisted of nine individuals in team sports that were considered as high performers (good/successful). Hence, also the concept of high performance was clarified with competence, expertise and talent literature. The study is qualitative and face-to-face interviews were chosen. The data was analyzed with Grounded Theory principles and theory elaboration. This thesis pointed out similarities and differences between the respondents´ answers (good/successful, inexperienced/experienced). Thus, the analysis clarified that there are different attitudes to learning and different learner profiles in sports context. Also, it became clear that some informal learning mechanisms are more used than others. Secondly, based on the most crucial differences, Typology of Talentum was formulated based on Le Deist & Winteron´s (2005, 39) Typology of holistic competence. Some variables of informal learning seemed to constitute the Meta-competence of Typology that ultimately causes the differences in individual performance and success. The results can be transferred to business context because meta-competence is transferable by nature.